Influence of Motivation and Job Satisfaction on Teacher Creativity in SMA Negeri Region II Jakarta Barat - Rajindra, Daru; Karnati, Neti; Soefijanto, Totok Amin (Universitas Malikussaleh, 2020)
This study aims to determine: (1) The direct effect of motivation on creativity; (2) the direct effect of Job Satisfaction on Creativity; and (3) the direct influence of motivation on job satisfaction. This study uses a survey method with a quantitative approach which is carried out using a path analysis technique. The unit of analysis in this study was all ASN Educators at SMA Negeri Region II Jakarta Barat with a sample size of 98 people selected with regard to a level in the population element (stratified random sampling). The results showed that: (1) there was a positive direct effect between motivations on creativity; (2) there is a positive direct effect between job satisfactions on creativity; and (3) there is a positive direct effect between motivations on job satisfaction.